Toward a Tweet Typology: Contributory Consumer Engagement With Brand Messages by Content Type. Issue 2 (2nd July 2016) - Vargo, Chris J.
ABSTRACT: This study assesses brand messages on Twitter (i.e., tweets broadcasted by a brand) and the contributory engagement a tweet receives. It presents a typology for brand messages that accounts for 92.6% of messages found. Findings offer mild support for self-concept and self-enhancement as drivers of engagement. This research also tests assumptions made by marketers regarding social content. Brand messages that promoted giveaways positively influenced engagement, giving support to Berger's (2012) behavioral residue claim. Brand messages that mentioned popular culture events and current holidays positively influenced engagement, suggesting that brands that humanize do see benefits. Finally, promotional messages negatively influenced engagement, suggesting that consumers are skeptical of product information that comes directly from brands.